The Pro-Climate Policy Carbon Tax, Is It Also Pro-Poor Policy? - Sutisna, Irwan (Bappenas Working Papers, 2023)
The Indonesian government introduced a carbon tax on April 1st, 2022. For the first stage, a carbon tax of IDR 30 per kilogram of CO2 will be applied to the coal-fired Steam Power Plant (PLTU) using a cap-and-tax mechanism. This study analyzes the impact of carbon tax policies according to different economic structures. Which region and sector are most affected? Furthermore, what is the effect of the carbon tax policy on economic growth, the unemployment rate, and poverty? There is a potential carbon tax revenue of IDR 5,846 billion. However, due to the cap-and-tax scheme, this study only allocates a potential tax revenue of IDR 1,000 billion. This potential tax revenue will be injected into further simulations. The first simulation shows that West Papua, East Kalimantan, and South Sumatra are the most severely affected provinces. It is rational since the coal mining and coal processing industries dominate their economy. Provinces with significant agriculture shares, such as the Special Region of Yogyakarta, North Sumatra, and West Sumatra, are the least affected by the policy. Simulation II is done by reallocating carbon tax revenues to the agricultural sector. The result shows that, although GDP increased by IDR 1,299.41 billion (0.0084%), it is not enough to shift the economy back to its previous state. On the other hand, although the economy continues to contract, the unemployment rate has decreased. The carbon tax has put 5,116 people out of work, mainly workers in the mining and coal processing sectors, and therefore, the unemployment rate increased by 0.0039%. However, the reallocation of tax revenues to the agricultural sector creates 23,483 new jobs, bringing unemployment down by 0.0183%. Finally, although economic growth is still slightly declining (-0.0112%), unemployment, poverty, and inequality are improving.